THE EFFECT OF HEALTH EDUCATION USING THE LEAFLET MEDIA ON ANXIETY LEVELS IN PRE OPERATION PATIENTS HOSPITAL AT UNGARAN - Fitria Annisa Rizki; Mugi Hartoyo; Sudiarto Sudiarto (JENDELA NURSING JOURNAL, 2019)
Background: Surgery will cause anxiety. One way to reduce anxiety in preoperative patients is through health education using leaflet media. Leaflets are pieces of paper that contain writing and images to convey a message and are easy to carry.Purpose: This study was to analyze the effect of health education using leaflet media on anxiety levels in preoperative patients at Ungaran Hospital.Methods: This study used Quasi-Experiment with the design of two group pre-post. Bivariate analysis using the Wilcoxon test. The sample amounted to 30 respondents consisting of 15 respondents in the intervention group and 15 respondents in the control group using the Consecutive Sampling approach that met the inclusion criteria. Anxiety level assessment was given twice before and after treatment and anxiety levels were measured using the HARS (Hamilton Anxiety Rating Scale) questionnaire.Results: The results showed that there was an effect of health education using leaflet media on anxiety levels (p=0,001) and there was an effect of health education without leaflets on anxiety levels (p=0,001). The post-test scores of the intervention group 9,13 and the control group 15,27.Conclusion: Health education using leaflet media can be applied as an alternative to delivering information before surgery to reduce anxiety.